The stress protein HSP70 from the marine sponge Thenea muricata. (13th January 2016) - Vallmann, K.; Kivisild, C.; Lopp, A.; Rapp, H.T.; Kelve, M.
Abstract : The members of the heat shock protein 70 ( HSP70) family are among the most conserved and widely studied stress proteins. The transcription and translation levels of HSP70 genes have also been studied in several marine and freshwater sponges as molecular markers to characterize the response of sponges to various types of physiological or environmental stress conditions. Furthermore, HSP70 protein sequences have been used in phylogenetic analysis of prokaryotes and eukaryotes. In this study, the expression of HSP70 genes in the marine sponge Thenea muricata during long-term cultivation under laboratory conditions was described at the protein and mRNA levels. Though there are many studies about distribution and morphology of T. muricata, few biochemical and molecular data can be found in the literature. HSP70 gene data for several sponge species have been deposited in the NCBI database, however, those for T. muricata are not available. Therefore, HSP70 genes were characterized in this sponge. Several proteins of the HSP70 superfamily which might be induced by stress, were present in T. muricata .